Keefektifan Konseling Kognitif Restructuring dalam Mengurangi Gejala Kecemasan Pada Remaja - Arsini, Yenti; Aisyah, Siti; Nurfaridah, Kharisma (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Adolescence is a transition period from childhood to early adulthood. According to Erik Erikson, adolescence is synonymous with the process of finding one’s identity versus identity confusion. At this time, teenagers must decide who they are, what their circumstances are and what goals they want to achieve. Teenagers deliberately carry out various experiments in an effort to find their compatibility with the world. In this process, teenagers experience various identity conflicts. Genetic factors play a role in a person’s susceptibility to experiencing anxiety, because if there is a history of anxiety in the family, the risk of experiencing anxiety disorders can be higher. Traumatic experiences, especially in childhood, often trigger the development of anxiety. Meanwhile, environmental stress such as financial, work or relationship problems can trigger anxiety. According to Ellis, the cognitive restructuring technique is Cognitive Restructuring, which focuses on efforts to identify and change the client’s negative thoughts or irrational self-statements and beliefs into positive and rational thoughts. The purpose of this discussion is how to change the way of thinking of a teenager who is currently experiencing increasing anxiety or stress, such as being unable to change his way of thinking and mental patterns properly so that his cognition can be straightened out positively using Cognitive Behavior Therapy (CBT), a cognitive restructuring.